MENDORONG KEPEMIMPINAN GLOBAL BERBASIS BUDAYA DI UPT SDN 03 PANCUNG SOAL: TINJAUAN PERMASALAHAN, KONSEP, DAN INOVASI - Weni Yulastri; Eka Maharani Putri; Hosman; Adellar Prasetya; Yulia Agus Fetri Weni; Elmasi Tri Oktaviani; Firman Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Culturally-based global educational leadership requires a deep understanding of cultural diversity, local and global integration, as well as adequate multicultural competencies. This study explores the challenges of such leadership at UPT SDN 03 Pancung, such as the lack of cultural literacy, the dominance of majority cultures, and communication barriers, along with an analysis of the background of these issues. Based on a review of strategies from national and international journals, this research employs a qualitative descriptive method aided by documentation and reflective interviews. The results show the effectiveness of culturally responsive and transformational leadership models, as well as concrete innovations such as cultural corners, weekly themes "Keminangkabauan", community collaboration, and digital storytelling. This concept has the potential to strengthen students' identities and equip them with global competencies.